Nitrification and denitrification processes in a zero-water exchange aquaculture system: characteristics of the microbial community and potential rates - Niu, Shuhui; Zhang, Kai; Li, Zhifei; Wang, Guangjun; Li, Hongyan; Xia, Yun; Tian, Jingjing; Yu, Ermeng; Gong, Wangbao; Xie, Jun (Frontiers in Marine Science, 2023)
​The zero-water exchange aquaculture has been identified as a promising method of farming to decrease the environment pressure of aquaculture and to increase profits. However, the ecological functions (e.g., nitrogen removal) and microbial biodiversity of the zero-water exchange pond aquaculture system are relatively understudied. In the present study, the zero-water exchange pond aquaculture system were constructed to investigated the microbial communities, sediment potential nitrification and denitrification production rates. And five functional genes (AOA amoA, AOB amoA, nirS, nosZ, and hzsB) were used to quantify the abundance of nitrifying and denitrifying microorganisms. The results showed that the sediment of the system had excellent potential nitrification-denitrification performance, with potential nitrification and denitrification rate were 149.77-1024.44 ng N g−1 h−1 and 48.32-145.01 ng N g−1 h−1, respectively. The absolute copy numbers of nitrogen functional genes and total bacterial 16S rRNA were 1.59×105-1.39×109 and 1.55×1010-2.55×1010copies g−1, respectively, with the dominant phyla, i.e., Proteobacteria, Actinobacteriota, Chloroflexi, Cyanobacteria, and Firmicutes. The relative abundances of the genera related to nitrification and denitrification, varied from 0.01% to 0.79% and from 0.01% to 15.54%, respectively. The potential nitrification rate was positively related to the sediment TOC concentration; and the potential denitrification rate had a positive correlation with sediment nitrate concentration. The genera Bacillus positively correlated with sediment NO3‐-N concentration, whereas Flavobacterium and Shewanella positively correlated with sediment NH4+-N concentration, which could be the functional bacteria for nitrogen removal. These findings may shed light on quantitative molecular mechanisms for nitrogen removal in zero-water exchange ponds, providing a sustainable solution to nitrogen pollution problem in the freshwater aquaculture ecosystems.